2021
DOI: 10.1007/s10554-021-02358-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparing left ventricular mechanical dyssynchrony between diabetic and non-diabetic patients with normal gated SPECT MPI

Abstract: Introduction; the aim of this study was to employ phase analysis to diagnose left ventricular mechanical dyssynchrony (LVMD)in asymptomatic patients with diabetes mellitus type 2 and normal perfusion study to prevent diabetic cardiomyopathy.Methods & materials; Ninety-three consecutive patients with known type 2 diabetes and 81 age-and gender-matched patients without diabetes who were candidates for SPECT-MPI were considered as the control group. The presence of LVMD as an indicator of cardiomyopathy-was deter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…LVSD existed in T2DM patients with normal myocardial perfusion and normal LVEF, which is also known as subclinical myocardial damage and challenging to diagnose early ( 23 , 24 ). Previous studies based on SPECT-MPI have demonstrated that 23–28% of T2DM patients with normal LVEF and normal myocardial perfusion had the presence of LVSD ( 19 , 22 ), which was similar to our findings. A large community-based cohort study found that patients with subclinical myocardial damage have a significantly increased risk of HF and all-cause mortality than those without subclinical myocardial damage ( 25 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…LVSD existed in T2DM patients with normal myocardial perfusion and normal LVEF, which is also known as subclinical myocardial damage and challenging to diagnose early ( 23 , 24 ). Previous studies based on SPECT-MPI have demonstrated that 23–28% of T2DM patients with normal LVEF and normal myocardial perfusion had the presence of LVSD ( 19 , 22 ), which was similar to our findings. A large community-based cohort study found that patients with subclinical myocardial damage have a significantly increased risk of HF and all-cause mortality than those without subclinical myocardial damage ( 25 ).…”
Section: Discussionsupporting
confidence: 92%
“…Generalized additive model (GAM) and cubic spline smoothing technique were performed to evaluate the association between EFV and LVSD in T2DM patients. Multivariable logistic regression models were produced to assess the association between EFV and LVSD; three models were generated: (I) a univariable model with EFV as a predictor; (II) multivariable-adjusted model 1, adjusted for age and sex; (III) multivariable-adjusted model 2 was constructed based on our team’s interpretation of a broad review of the literature, and adjusted for age, sex, BMI, DM duration, presence of hypertension, active smoking, FBG, HbA1c, and TG ( 19 , 21 , 22 ). Receiver operating characteristic (ROC) curve analysis was performed to determine the predictive value of EFV for LVSD.…”
Section: Methodsmentioning
confidence: 99%
“…Similar studies comparing diabetes and nondiabetes patients with normal myocardial perfusion and systolic function have focused on other parameters of the G-SPECT MPI. Studies assessing dyssynchrony in patients with diabetes showed no significant difference in dyssynchrony parameters of G-SPECT MPI in diabetes and nondiabetes patients in general, whereas a significant correlation between long-standing diabetes and dyssynchrony has been reported [24,25]. However, a recent study reported a correlation between ES-SI and ED-SI in the presence of diabetes [19].…”
Section: Discussionmentioning
confidence: 99%